Human Capital Development Strategy in Supporting Employee Performance Improvement Usedcar Advisor - Jedil; Akhmad; Rusydi (Al-Kharaj: Journal of Islamic Economic and Business, 2026)
This study aims to analyze human capital development strategies in supporting the improvement of the performance of Usedcar Advisor employees at Kalla Toyota Trust Makassar. The background of this research departs from the low effectiveness of training and mastery of used vehicle appraisal techniques which has implications for the increase in the number of old stock and the decline in the company's operational efficiency. The research uses a descriptive qualitative approach with data collection techniques through observation, interviews, and documentation studies on employees and company management. The results of the study show that the human capital development strategy at Kalla Toyota Trust has included training, competency development, and career management, but the implementation has not been optimal in the field of implementation. The main inhibiting factors include the lack of post-training assistance and the lack of a measurable performance evaluation system. With the optimization of continuous training strategies and the improvement of competency-based work culture, the performance of Usedcar Advisor employees can be significantly improved